ANALISIS HUKUM ISLAM PERLINDUNGAN HUKUM KEKERASAN TERHADAP PEREMPUAN DAN ANAK DI KABUPATEN BENGKALIS - Yuni Dhea Utari; Irlina Dewi; Muhammad Ilham (TAQNIN: Jurnal Syariah dan Hukum, 2023)
Violence against women and children in Indonesia has become a serious concern within the Indonesian government, one of which is in Bengkalis district. the method used in this research is descriptive analysis method with a qualitative approach. Legal Protection Efforts for Violence Against Women and Children in Criminal Acts contained in the Bengkalis Police, namely socialization or counseling for the community, giving / distributing brochures and banners about anti-violence against women and children, then there must be cooperation with the police, prosecutors and the women's empowerment and child protection services in Bengkalis Regency, as speakers at seminars or outreach related to violence against women and children. In addition to efforts, there must be several obstacles, which include one of these obstacles, the difficulty of finding information due to the difficulty of honesty from the victim due to internal oppression so that news does not spread